ECONOMIC SITUATION OF EASTERN POLAND AND POPULATION MIGRATION MOVEMENT - Pietrzak, Michał Bernard; Chrzanowska, Mariola; Wilk, Justyna (Metody Ilościowe w Badaniach Ekonomicznych, 2013)
The aim of this paper is to examine population migration flows in relation to the eastern Poland and its economic situation. The empirical study refers to the period 2008-2010 corresponding to global financial and economic crisis which affected the intensity and directions of internal migrations in Poland. Ratio analysis, as well as taxonomical analysis was applied in the research.